Proceedings of SPE Annual Technical Conference and Exhibition 1989
DOI: 10.2523/19691-ms
|View full text |Cite
|
Sign up to set email alerts
|

Foam Performance Under Reservoir Conditions

Abstract: Seabed data acquisition methods offer numerous advantages over towed streamer data. These advantages can lead to improved static and dynamic reservoir characterization. By recording complete vector field data at the sea floor with full azimuth acquisition improved shallow resolution, signal-to-noise ratio, spectral content, deep imaging and 3D illumination can be achieved. Also in the presence of obstacles such as production facilities a regular coverage can be assured.Autonomous node technology has been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…It was also concluded that effective foam can be generated in an oil-wet environment provided appropriate foaming agents are selected. [33] Osterloh and Jante (1992) studied the effects of gas and liquid velocities on steady-state foam flow in porous media at high temperatures. Experiments were performed at 150 o C using nitrogen gas along with C16-18 alpha-olefin-sulfonate (AOS) and pressure gradients were measured in a 6.2 mD sand pack over a wide range of fractional flows and gas and liquid velocities.…”
Section: Effect Of Foam On Gas Mobilitymentioning
confidence: 99%
“…It was also concluded that effective foam can be generated in an oil-wet environment provided appropriate foaming agents are selected. [33] Osterloh and Jante (1992) studied the effects of gas and liquid velocities on steady-state foam flow in porous media at high temperatures. Experiments were performed at 150 o C using nitrogen gas along with C16-18 alpha-olefin-sulfonate (AOS) and pressure gradients were measured in a 6.2 mD sand pack over a wide range of fractional flows and gas and liquid velocities.…”
Section: Effect Of Foam On Gas Mobilitymentioning
confidence: 99%
“…Foam stability varies widely in the presence of different oil types as has been observed by some researchers (Suffridge et al, 1989;Novosad, 1990, 1992). However, surfactant type is also a contributing factor to the effect of oil presence.…”
Section: The Effect Of Oil On the Two Foam-flow Regimesmentioning
confidence: 95%
“…The effect of oil on foam depends on the interaction between the oil and the surfactant (Suffridge et al, 1989;Meling and Hanssen, 1989). Therefore, both the oil and surfactant properties may be the important factors.…”
Section: The Effect Of Oil On the Two Foam-flow Regimesmentioning
confidence: 99%
“…Contaminants such as methane and nitrogen significantly increase the CO 2 minimum miscibility pressure, and H 2 S, C 2 H 6 or intermediate hydrocarbons have the opposite effect. [28] Figure 6. Slim-tube oil recoveries for fixed oil composition and temperature over pressure [12] Improved oil recovery by CO 2 flooding results from: In miscible flooding all the above phenomena are responsible for improving the oil recovery but the first two outweigh the rest.…”
Section: -5-1-minimum Miscibility Pressure (Mmp)mentioning
confidence: 99%